(untitled) (Journal of Health, Technology and Science (JHTS), 2025)
Diabetes mellitus is a chronic metabolic disease characterized by increased blood glucose levels. Diabetes mellitus can be treated through medical or herbal means. One herbal plant that can lower blood glucose levels is the leaves of the cherry tree. This study aims to determine the difference in blood glucose levels before and after consuming a decoction of cherry leaves (Muntingia calabura) in patients with diabetes mellitus. This research uses a quantitative approach with a one-group pretest-posttest design. The sample consists of 30 people selected using purposive sampling technique. Blood glucose levels were measured using the POCT method before and after a 7-day intervention. The Shapiro-Wilk normality test showed that the data were not normally distributed, so the analysis was conducted using the Wilcoxon Sign-Rank test. The results show a decrease in blood glucose levels after the intervention, with a p-value < 0.05, indicating a significant difference between glucose levels before and after consuming cherry leaves. Conclusion: The infusion of cherry leaves has the potential to be an alternative for lowering blood glucose levels in patients with diabetes mellitus